ZOOPLANKTON COMMUNITY IN LAMALERA SEA AND SAWU SEA, EAST NUSA TENGGARA - Nurul Fitriya; Muhammad Lukman (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2013)
Zooplankton community was studied in Lamalera Sea and Sawu Sea during DIKTI-P2O LIPI Expedition from 19 – 30 July 2011. Besides being a potential fishing ground, the Lamalera sea and Sawu Sea have been a migration path for Cetacean (large marine mammals), particularly during the southeast monsoon season. The purposes of this study were to investigate community structure, abundance, and spatial distribution of zooplankton in the Lamalera Sea and the Sawu Sea.  Plankton samples were collected from 23 stations, by NORPAC 300 µm-net that was vertically hauled from maximum 200 meter depth up to the surface water. The result showed that there were 45 taxa of zooplankton, which was dominated by copepods . The abundance of the zooplankton between 491 - 4537 individu/m3. Average diversity index and evenness values were 1.59 ± 0.21 and 0.50 ± 0.04, respectively. In this area, Creel has been found in all research stations but the abundance was small. Species composition was relatively the same between sampling stations suggesting that there was no different in composition between north and south parts, which virtually comprise of different water masses. It showed that spatial distribution of zooplankton was relatively  wide-reaching. Keywords: zooplankton, copepoda, creel, Lamalera sea, and Sawu Sea.